2016
DOI: 10.4236/aad.2016.53008
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Effects of a Combination of Sideritis and Bacopa Extract (memoLoges<sup>®</sup>) in 32 Subjects Suffering from Mild Cognitive Impairment. A Double-Blind, Randomized, Placebo-Controlled, 2-Armed Study with Parallel Design

Abstract: Mild cognitive impairment (MCI) can be regarded as a non-demented transitional stage during the development of Alzheimer's disease. Early recognition of this stage might increase the chance of prevention by early treatment. Within a pilot study, two plant-derived preparations and mixtures thereof were tested successfully in subjects suffering from MCI. A combination of Sideritis scardica and Bacopa monnieri extract (memoLoges ®) was chosen now for a repetitive dosing during 4 weeks. Thirty-two subjects aged 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…This implicates that Sideritis scardica extract might be able to improve cognitive functions. At some matter of fact exactly this has been shown in a human clinical study already after a single intake of 500 mg of identical Sideritis scardica extract [10].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This implicates that Sideritis scardica extract might be able to improve cognitive functions. At some matter of fact exactly this has been shown in a human clinical study already after a single intake of 500 mg of identical Sideritis scardica extract [10].…”
Section: Discussionmentioning
confidence: 55%
“…From all this knowledge about AMPA receptors is can be concluded that Sideritis scardica extract is able to improve cognition and mental work as well as prevent age-dependent decline of mental fitness. A recent clinical study performed in mildly cognitively impaired subjects over 4 weeks revealed a positive effect by treatment with a mixture of Sideritis scadica extract with Bacopa extract [17]. In addition to antidementive treatment also at least an add-on treatment during ischaemic stroke might be considered [18].…”
Section: Discussionmentioning
confidence: 99%
“…MemoLoges ® has been clinically tested in subjects suffering from mild cognitive impairment [14] [15]. A dominant feature after intake of 2 capsules memoLoges ® consisted in significant increases of alpha 1 spectral power in most of the brain areas except for the occipital lobe and parts of the frontal lobe (electrode positions F 3 and F 4 ).…”
Section: Memologes ®mentioning
confidence: 99%
“…S. scardica extracts were able to improve the mental performance of healthy subjects under stress conditions and of subjects suffering from mild cognitive impairment (MCI), which is a precursor of AD ( Behrendt et al, 2016 ; Dimpfel, Schombert & Biller, 2016b ). A double-blind, randomized, and placebo-controlled clinical trial currently demonstrates a significant effect of a combination of S. scardica and Bacopa monnieri extract (memoLoges®) on the mental performance of subjects suffering from MCI ( Dimpfel et al, 2016c ).…”
Section: Introductionmentioning
confidence: 99%